Does Cyclic Stress Play a Role in Highly Crosslinked Polyethylene Oxidation?. Issue 3 (March 2015) - Medel, Francisco; Kurtz, Steven; MacDonald, Daniel; Pascual, Francisco Javier; Puértolas, José Antonio
Abstract: Background: Minimizing the impact of oxidation on ultrahigh‐molecular‐weight polyethylene components is important for preserving their mechanical integrity while in vivo. Among the strategies to reduce oxidation in modern first‐generation highly crosslinked polyethylenes (HXLPEs), postirradiation remelting was considered to afford the greatest stability. However, recent studies have documented measurable oxidation in remelted HXLPE retrievals. Biologic prooxidants and physiologic loading have been proposed as potential mechanisms. Questions/purposes: In our pilot study, we asked: (1) Does cyclic stress induced by wear or (2) by cyclic compression loading increase oxidation and crystallinity of remelted HXLPE? (3) Does oxidative aging reduce the wear resistance of remelted HXLPE? Methods: Remelted and annealed HXLPE prisms (n = 1 per test condition) were tested in a wear simulator for 500, 000 cycles. After wear testing, some samples were subjected to accelerated aging and then wear‐tested again. Wear track volumes were characterized by confocal microscopy. Thin films (200‐μm thick) were microtomed from wear prisms and then used for Fourier transform infrared spectroscopy oxidation and crystallinity assessments. Remelted HXLPE compression cylinders (n = 1 per test condition) were subjected to fatigue experiments and similar oxidation characterization. Results: Remelted HXLPE qualitatively showed low oxidation indices (≤ 1) when subjected either to cyclic loading or aging alone. However, oxidation levels almost doubled in near‐surface regions when remelted HXLPE samples underwent consecutive cyclic loading, artificial aging, and cyclic loading steps. The type of loading (wear versus compression fatigue) appeared to not affect the oxidation behavior in the studied conditions. Annealed HXLPE showed higher oxidation (oxidation index > 3) than remelted HXLPE and delamination wear. No delamination wear was observed in remelted HXLPE in agreement with its comparatively low oxidation levels (oxidation index < 3). Conclusions: With the numbers available in our pilot study, the findings suggest that cyclic stress arising from a wear process or from cyclic compression may trigger the loss of oxidative stability of remelted HXLPE and contribute to synergistically accelerate its progression. Further studies of the effect of cyclic stress on oxidation of remelted HXLPE are needed. Clinical Relevance: Retrieval studies are warranted to determine the natural history of the in vivo oxidation and wear behavior of first‐generation, remelted HXLPE.